The CIPP Model In Training Program Evaluation: How Effective Is It? - Mihnatuz Zahroh; Lamijan Hadi Susarno; Bachtiar Sjaiful Bachri (Journal of Educational Technology Studies and Applied Research, 2025)
Evaluating training programs is crucial for ensuring their effectiveness and long-term impact. Traditional evaluation models, such as the Kirkpatrick and ROI models, have been widely used but face limitations in assessing the entire training process, particularly in tracking implementation challenges and long-term impact. A key gap in research is the inconsistent implementation and validation of the CIPP (Context, Input, Process, Product) model across different training settings. This study systematically reviews the effectiveness of the CIPP model in training program evaluation from 2015 to 2025, analyzing ten open-access journal articles. The findings reveal that while the CIPP model provides a structured and comprehensive framework for training evaluation, challenges persist, including inconsistent application, resource constraints, and the need for better feedback mechanisms. The results highlight the necessity of refining training assessments through standardized implementation, improved evaluator training, and digital integration. These insights are critical for policymakers, educators, and corporate trainers in optimizing training effectiveness and fostering continuous improvement.